Optimization of active layer morphology by small-molecule donor design enables over 15% efficiency in small-molecule organic solar cells. Issue 23 (3rd June 2021) - An, Cunbin; Qin, Yunpeng; Zhang, Tao; Lv, Qianglong; Qin, Jinzhao; Zhang, Shaoqing; He, Chang; Ade, Harald; Hou, Jianhui
Abstract : Two conjugated small molecules with different conjugated side chains were synthesized to study their photovoltaic performances. Abstract : Molecular innovation is highly important to achieve highly efficient small-molecule organic solar cells (SMOSCs). Herein, we report two small-molecule donors, namely, B3T-T and B3T-P, which differ only in their conjugated side chains: the former with a thienyl group and the latter with a phenyl unit. Surprisingly, both small-molecule donors show distinct electron density distribution and electrostatic potential along the conjugated backbone. B3T-P has a much higher dipole moment (0.920 D) than that of B3T-T (0.237 D). In SMOSCs, the B3T-T :BO-4Cl -based device shows a decent power conversion efficiency (PCE) of 11.1%. In contrast, the B3T-P :BO-4Cl -based device gives an outstanding PCE of 15.2%, which is one of the highest values among SMOSCs. Compared to the B3T-P -based device, although the B3T-T -based device has a large enough driving force for exciton separation and an extremely low non-radiative recombination voltage loss (0.168 V) for achieving high open-circuit voltage, the large domain size (63 nm) and low domain purity in the B3T-T :BO-4Cl -based device results in a relatively low short-circuit current density and fill factor, thus giving a low PCE. This result may pave the way to rationally design SM donors for highly efficient SMOSCs.